Effectiveness of base‐of‐skull immobilization system in a compact proton therapy setting. (6th April 2018) - Shafai‐Erfani, Ghazal; Willoughby, Twyla; Ramakrishna, Naren; Meeks, Sanford; Kelly, Patrick; Zeidan, Omar
Abstract: Purpose: The purpose of this study was to investigate daily repositioning accuracy by analyzing inter‐ and intra‐fractional uncertainties associated with patients treated for intracranial or base of skull tumors in a compact proton therapy system with 6 degrees of freedom (DOF) robotic couch and a thermoplastic head mask indexed to a base of skull (BoS) frame. Materials and methods: Daily orthogonal kV alignment images at setup position before and after daily treatments were analyzed for 33 patients. The system was composed of a new type of thermoplastic mask, a bite block, and carbon‐fiber BoS couch‐top insert specifically designed for proton therapy treatments. The correctional shifts in robotic treatment table with 6 DOF were evaluated and recorded based on over 1500 planar kV image pairs. Correctional shifts for patients with and without bite blocks were compared. Results: Systematic and random errors were evaluated for all 6 DOF coordinates available for daily vector corrections. Uncertainties associated with geometrical errors and their sources, in addition to robustness analysis of various combinations of immobilization components were presented. Conclusions: Analysis of 644 fractions including patients with and without a bite block shows that the BoS immobilization system is capable of maintaining intra‐fraction localization with submillimeter accuracy (in nearly 83%, 86%, 95% of cases along SI, LAT, and PA, respectively) in translational coordinates and subdegree precision (in 98.85%, 98.85%, and 96.4% of cases for roll, pitch, and yaw respectively) in rotational coordinates. The system overall fares better in intra‐fraction localization precision compared to previously reported particle therapy immobilization systems. The use of a mask‐attached type bite block has marginal impact on inter‐ or intra‐fraction uncertainties compared to no bite block.